Pharmaceutical care in oncology: An integrative literature review (Research, Society and Development, 2021)
Cancer is characterized as a set of diseases in which abnormal cells grow and spread uncontrollably. Therefore, it is necessary to perform the pharmaceutical care that has become essential during cancer treatment, as the pharmacist is the professional responsible for solving doubts and providing guidelines for the correct use of medicines, as well as monitoring possible adverse reactions or drug interactions. This integrative review aimed to evaluate the available bibliographies on pharmaceutical care in oncology.The research was carried out between the years 2016 to 2020 using the keywords "pharmaceutical care", "pharmaceutical care", "oncology", "chemotherapy", "pharmaceutical care", "cancer patient" and "cancer". The databases used were: Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), in the CAPES Journal Portal and in Google Scholar. The inclusion criteria used were complete articles available electronically, written in Portuguese and appropriate to the chosen theme. After using the inclusion and exclusion criteria mentioned in the methodology of this study, 16 articles were included in this integrative literature review, which deal with pharmaceutical care in cancer patients. Of these, 4 were found on the CAPES Journal Portal, 2 on the SciELO database and 10 on Google Scholar; the other bases surveyed did not obtain results included. Although there are already many studies on pharmaceutical care in the literature, there are still few health establishments that adequately provide this type of service or that have it implemented. Therefore, the need for future work to verify the institutions that already have their pharmaceutical care instruments in use.